2017
DOI: 10.2172/1342718
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Material and Test reactor Fuel in an H-Canyon Dissolver

Abstract: In an amended record of decision for the management of spent nuclear fuel (SNF) at the Savannah River Site, the US Department of Energy has authorized the dissolution and recovery of U from 1000 bundles of Al-clad SNF. The SNF is fuel from domestic and foreign research reactors and is typically referred to as Material Test Reactor (MTR) fuel. Bundles of MTR fuel containing assemblies fabricated from U-Al alloys (or other U compounds) are currently dissolved using a Hg-catalyzed HNO 3 flowsheet. Since the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The overall dissolution rate of Al 1100 alloy is approximately 19 mg/min/cm 2 (based on Experiment 106) starting with a 7M HNO 3 solution and adding 0.002M Hg at boiling. 11 The highest dissolution rate for the stainless steel was 0.02 mg/min/cm 2 . Based on the overall dissolution rate, the stainless steel is approximately 950 times slower than the Al-1100, which tracks with the comparison based on offgas generation.…”
Section: Rates Of Dissolutionmentioning
confidence: 90%
“…The overall dissolution rate of Al 1100 alloy is approximately 19 mg/min/cm 2 (based on Experiment 106) starting with a 7M HNO 3 solution and adding 0.002M Hg at boiling. 11 The highest dissolution rate for the stainless steel was 0.02 mg/min/cm 2 . Based on the overall dissolution rate, the stainless steel is approximately 950 times slower than the Al-1100, which tracks with the comparison based on offgas generation.…”
Section: Rates Of Dissolutionmentioning
confidence: 90%
“…In previous flowsheets developed for the dissolution of HFIR 14 and MTR fuels 13 , Daniel et al demonstrated that Al 1100 provided a bounding estimate for the generation of H2 and was subsequently used as a surrogate for these fuels. Although, the development of a new flowsheet is not required for the dissolution of SNF prior to the dissolution of LEU ingots in H-Canyon, an experimental Al 1100 dissolution was performed as part of the flowsheet demonstration.…”
Section: Surrogate Materialsmentioning
confidence: 99%
“…The dissolution of the Al 1100 alloy coupon was performed using the same general flowsheet used in H-Canyon for the dissolution of MTR and HFIR fuel. 13,14 A summary of the objective and dissolution conditions for each experiment are provided in Table 2. All experiments were performed at the boiling point of the solution except for Experiment 86 which was performed at room temperature.…”
Section: Dissolution Experiments For Offgas Characterizationmentioning
confidence: 99%
See 2 more Smart Citations